2018
DOI: 10.1002/asia.201801224
|View full text |Cite
|
Sign up to set email alerts
|

Recent Advancements in Graphene‐Based Supports of Metal Complexes/Oxides for Epoxidation of Alkenes

Abstract: In the past decade, there has been great progress in the preparation and catalytic applications of graphenesupported metal complexes/oxide catalysts. Graphene-based materials have attracted tremendous research interest owing to special physicochemical properties, for example, unique two-dimensional structure, high theoretical specific surface area, high electrical conductivity,a nd outstanding acid-base resistance properties. Graphene-supported metal complexes/ oxides have been extensively investigated, and ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
10
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 83 publications
0
10
0
Order By: Relevance
“…For the epoxidation of allylic alcohols or olefins with H 2 O 2 as an oxygen source, the use of catalysts including metal oxides, 10,11 transition-metal compounds, 12−14 and molecular sieves 15−17 is very common. Especially, titanium silicalite (TS-1) has been found to be a unique material that enables effective transformation of olefins into epoxides since the 1980s.…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For the epoxidation of allylic alcohols or olefins with H 2 O 2 as an oxygen source, the use of catalysts including metal oxides, 10,11 transition-metal compounds, 12−14 and molecular sieves 15−17 is very common. Especially, titanium silicalite (TS-1) has been found to be a unique material that enables effective transformation of olefins into epoxides since the 1980s.…”
Section: ■ Introductionmentioning
confidence: 99%
“…For the epoxidation of allylic alcohols or olefins with H 2 O 2 as an oxygen source, the use of catalysts including metal oxides, , transition-metal compounds, and molecular sieves is very common. Especially, titanium silicalite (TS-1) has been found to be a unique material that enables effective transformation of olefins into epoxides since the 1980s. In recent years, group V transition-metal catalysts have attracted immense attention in selective oxidation. , For example, the application of vanadium compounds in oxidation catalysis has been reported in many studies, including alkane oxidation, alcohol oxidation, olefin epoxidation, , lignin degradation by oxidation, etc .…”
Section: Introductionmentioning
confidence: 99%
“…The present potential approaches for replacing conventional methods normally involve peroxides as sacrificial oxidizing agents. Among the developed catalysts, heterogeneously transition-metal-based catalysts such as Co/Fe/Mn/W-based oxides are promising alternatives for their good oxidation activity, recyclable nature, and cost-effectiveness . For example, Liu et al reported the 79.7% yield and 82.7% selectivity of SO for the CoFe 2 O 4 catalyst using tertiary butyl hydroperoxide (TBHP) as an oxidant.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, GO has been widely researched as a promising catalyst carrier [16], mainly because of its unique two-dimensional planar structure (which is beneficial to improve the dispersion of catalytic active species on the surface), higher specific surface area (which is beneficial to increase its forces with active species and, to a certain extent, prevent the migration and leaching of active species in the reaction process), and the nanometer size effect (which can improve the catalytic reaction rate). In addition, the surface of GO contains a large amount of oxygen-containing active groups, such as carboxyl, hydroxyl, and epoxy groups, which are easy to chemically modify [17] and can react with noble metal catalysts and homogeneous ligands to obtain various supported catalysts with different coordination modes.…”
Section: Introductionmentioning
confidence: 99%